Pendampingan Pembentukan Kelompok Perlindungan Perempuan dan Anak (KP2A) Kelurahan Mataloko - Pare, Prisko Yanuarius Djawaria; Fono, Yasinta Maria; Rewo, Yosep Marsianus (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to establish the Women and Children Protection Group (KP2A) in Mataloko Village, Golewa District, Ngada Regency, as a preventive effort against violence toward vulnerable groups, particularly women and children. The activity was conducted on May 18, 2025, through socialisation and assistance in forming the KP2A, in collaboration with the Office of Women’s Empowerment and Child Protection of Ngada Regency, the Mataloko Village Government, and Golewa Police Sector. The implementation methods included disseminating relevant laws and regulations to group members and the community, as well as issuing an official decree by the village head for the formation of the KP2A. The outcomes achieved include the establishment of the KP2A organisation with a formal management structure, the allocation of a supporting operational budget, and the preparation of a structured work program for ongoing violence prevention activities. This program is expected to increase legal awareness among the community, minimise cases of sexual violence against women and children, and position Mataloko as a child-friendly village. This initiative demonstrates that violence prevention efforts should begin within families, supported by the local community and stakeholders.